Mobile app-based pain management education for ambulatory surgery patients in Denmark : A Legitimation Code Theory analysis - Hindhede, Anette Lykke; Moeller, Tom; Lassen, Karsten Lomholt ; 0000-0002-4633-0772; Dybdal, Bitten; Andersen, Christina Ingeborg (Patient Education and Counseling, 2025)
Objectives: This paper analyzes the educational content of the MinSmerte (MyPain) app, designed to educate patients on postoperative pain management after ambulatory surgery. It examines the complexity of instructional videos, investigating how these relate to the legitimacy claims constructed by educators – defined as assertions about the value of the information based on its relevance, authority, alignment with community norms. Patient feedback is explored to assess their perceptions of the app's effectiveness in facilitating knowledge building. Methods: The study involved an analysis of three instructional videos using the Semantics dimension of Legitimation Code Theory. Additionally, the Specialization dimension was used to analyse data from telephone interviews with 29 post-discharge patients, focusing on their perceptions of the app's accessibility, comprehensibility, and usability, in relation to their everyday pain management practices. Interviews included specific questions to evaluate patients’ health literacy levels and how those influenced their perception of accessibility, comprehensibility, and usability. Results: The instructional videos employed accessible language but varied in effectiveness. Some patients found the app beneficial for connecting with the hospital and tracking progress, while others faced challenges in navigation and clarity. Conclusion: Mobile apps for patient education hold significant potential for postoperative pain management. The study highlights the importance of customizing both content and technical aspects of the app to align with patients’ health literacy and their perceptions of accessibility, comprehensibility, and usability for optimizing the educational impact. Practice implications: Findings stress the importance of assessing health literacy in patient education apps to enhance patient experiences and promote knowledge building through a framework of socially just pedagogies. Legitimation Code Theory provides a valuable framework for understanding knowledge dynamics in app-based education, emphasizing the importance of patient involvement in the co-design process.
Keywords: Instructional videos; Knowledge building; Legitimation code theory; Patient education; Postoperative pain; Socially just pedagogy; Teaching material